Функції виконавчих органів місцевих рад України: сучасний стан та перспективи розвитку - Бальций Юрій Юрійович; Бальций Юрий Юрьевич; Bal'cij Jurij (My University, 2013)
The article investigates the features of functions of executive bodies of local councils of Ukraine. Established that the executive bodies of local councils carry out two groups of functions, namely its own and the functions of the executive.
Бальций Ю. Функції виконавчих органів місцевих рад України: сучасний стан та перспективи розвитку / Ю. Бальций // Юридичний вісник. - 2013. - № 1. - С. 52-57.
Keywords: місцеве самоврядування; виконавчі органи; місцеві ради; публічна влада; функції виконавчих органів; местное самоуправление; исполнительные органы; местные советы; публичная власть; функции исполнительных органов; local government; executive bodies; local Councils; public authority; the functions of the executive bodies